KORELASI SIFAT FISIK DAN KIMIA TANAH DENGAN INTENSITAS PENYAKIT BUSUK PANGKAL BATANG TANAMAN LADA / Correlation of Physical and Chemical Soil Characteristics with Intensity of Foot Rot Disease of Black Pepper - La Ode Santiaji Bande; Abdul Wahab; Bambang Hadisutrisno; Susamto Somowiyarjo; Bambang Hendro Sunarminto (Jurnal Penelitian Tanaman Industri, 2016)
Foot rot disease of black pepper caused by Phytophthora capsici is the most destructive disease in Southeast Sulawesi. The disease intensity is 61.2%. This disease is difficult to control because the pathogen is soil borne and influenced by various complex environmental conditions. The study aimed to determine the correlation of physical and chemical soil characteristics with disease intensity of foot rot of black pepper. Disease intensity was assessed from the subplots of black pepper plantation of 15x15 m2 consisting of 36-40 plants. Soil samples were randomly taken from the rhizosphere of the plants in each sub plot, mixed and taken as a composite. The physical and chemical analyses were conducted in the laboratory of Physics and Chemistry of the Faculty of Agriculture, Gajah Mada University. Disease intensity and soil characteristics were analyzed its correlation using a path analysis. The results showed that soil fertility in the study area was low. The path analyses indicated that physical and chemical properties that correlated with low disease intensity were high cation exchange capacity (CEC), base saturation (BS), potassium and phosphor available as well as moisture at field capacity, whereas those induced disease development were high content of clay fraction, sand fraction, porosity, total N, C-organic and salinity. The control strategy for foot rot disease in Southeast Sulawesi was possibly by increasing CEC, BS, potassium and phosphor available, as well as by improvement of soil texture that can lower high fraction of clay, sand and soil porosity